Impact dynamics and puncture failure of pressurized tank cars with fluid–structure interaction: A multiphase modeling approach. (April 2016) - Yu, Hailing; Jeong, David Y.
Highlights: Shell (side) impact tests were conducted on full scale, pressurized tank cars resulting in deformed or punctured tank cars. We developed finite element models for pressurized tank cars with fluid–structure interaction among gas, liquid and solid. We applied a stress triaxiality dependent fracture initiation criterion to predict tank car puncture under dynamic loading. We validated the finite element models developed in this paper with the full scale, side impact test data. The effect of various engineering factors on tank car puncture was studied quantitatively using the validated models. Abstract: This paper presents a computational framework that analyzes the effect of fluid–structure interaction (FSI) on the impact dynamics and puncture failure of pressurized commodity tank cars carrying hazardous materials. Shell (side) impact tests have been conducted on full scale tank cars resulting in deformed or punctured tank cars. A finite element (FE) modeling method is applied that explicitly simulates the three distinct phases in a tank car loaded with a liquefied substance: pressurized gas, pressurized liquid and solid structure. Furthermore, an equivalent plastic strain based fracture initiation criterion expressed as a function of stress triaxiality is adopted to depict the fracture behavior of the tank car steel material. The fracture initiation is implemented for ductile, shear and mixed fracture modes and followed by further material deterioration governed by a strain softening law. The force, displacement and impact energy results obtained from the FE analysis show good agreement with the corresponding shell impact test data. The simulations demonstrate that FSI plays a critical role in predicting the correct dynamics of tank car impact. The puncture resistance of a tank car, characterized as limit impact conditions in terms of puncture energy or puncture velocity, is further analyzed in shell impact scenarios. The puncture energy is shown to increase as the initial fluid pressure decreases, the tank car thickness increases or the effective impactor size increases. Quantitative correlations between puncture energy/velocity and each of these factors are obtained using the FE analysis method developed in this paper.